1976
DOI: 10.1192/bjp.128.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Self-Harm: A Follow-Up Study of 279 Patients

Abstract: Two-hundred-and-seventy-nine patients (103 men, 176 women) were followed-up 1-2 years after an act of non-fatal deliberate self-harm. Of 155 patients offered a psychiatric out-patient appointment at the time, only 68 completed the treatment. A further act of deliberate self-harm was committed by 26 men and 41 women within twelve months. The factors most highly associated with repetition were previous psychiatric treatment, a previous act of deliberate self-harm, and a criminal record. These factors held good f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
32
3
8

Year Published

1979
1979
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 6 publications
7
32
3
8
Order By: Relevance
“…In Finland, each person attempting suicide is recommended to be investigated and appropriate treatment arranged [16]. Furthermore, it is suggested that recognition and treatment of mental disorders, careful assessment of the risk factors for suicide, as well as aftercare of those with a high suicidal risk are the most important methods of preventing suicide [19,20].While our results accord with previous findings that the majority of suicide attempters are referred to aftercare (Table 1) [7,21] and have a health care contact during the year following the attempt, we found that one-third of attempters did not receive even the very minimum recommended aftercare during the month after the attempt. A previously recognised major mental disorder or active referral to aftercare were both powerful independent predictors of health care contact after the suicide attempt.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Finland, each person attempting suicide is recommended to be investigated and appropriate treatment arranged [16]. Furthermore, it is suggested that recognition and treatment of mental disorders, careful assessment of the risk factors for suicide, as well as aftercare of those with a high suicidal risk are the most important methods of preventing suicide [19,20].While our results accord with previous findings that the majority of suicide attempters are referred to aftercare (Table 1) [7,21] and have a health care contact during the year following the attempt, we found that one-third of attempters did not receive even the very minimum recommended aftercare during the month after the attempt. A previously recognised major mental disorder or active referral to aftercare were both powerful independent predictors of health care contact after the suicide attempt.…”
Section: Discussionsupporting
confidence: 86%
“…A contact subsequent to an attempt offers a chance for treatment intervention. Previous studies have investigated health care contacts either before or after the suicide attempt [6][7][8][9][10][11][12][13], but the pattern of all health care contacts both before and after the attempt has not been systematically studied in a large, representative sample of suicide attempters.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors associated with repetition in our study (except for several previous suicide attempts before index and early repetition) were psychiatric treatment at the index attempt, and having high suicide ideation and low global functioning at one month. Other studies have found that being in psychiatric treatment is associated with repetition of suicide attempt [10,12,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies use data collected at the index attempt. The following predictors for repetition within one year after index attempt have been identified; age 24 -54, single/divorced/ living alone, unemployed, lower social class, social isolation, female gender, criminal record, experience of physical violence, previous suicide attempt, cutting as method for index attempt, suicidal ideation, suicidal behaviour among relatives, depression and hopelessness, personality disorder, alcohol/ substance abuse, previous psychiatric treatment, referral to psychiatric treatment, use of psychotropic drugs, organic brain disorder, chronic somatic complaints [10,11,12,13,20,21,22]. Similar predictors have been found for repetition within 6 months [11,16,23].…”
Section: Introductionmentioning
confidence: 99%
“…Of these it is estimated that at least a third have reported a previous episode of self-harm and that 15-25% will repeat within three months (Buglass & Horton, 1974a;Morgan et al 1976;Bancroft & Marzack, 1977). The public health impact of parasuicide is therefore substantial: the burden on casualty, general medical and psychiatry services is considerable (Pallis et al 1975) and the risk of suicide is high (Rygnestad, 1988).…”
mentioning
confidence: 99%